TEMUAN FRAGMEN GERABAH SEBAGAI INDIKASI PERMUKIMAN KUNO DI SITUS BOROBUDUR - Agni Sesaria Mochtar (Berkala Arkeologi, 2013)
Borobudur temple has been famously known as one of the Indonesian heritage masterpiece. Various aspects of it had been studied thoroughly since the beginning of 20th century A.D. Those studies tended to be monumental centric, giving less attention to the cultural context of the temple and its surroundings. Settlement in the nearby places is one of the topics which not have been studied much yet; leaving a big question about how the settlement supported continuity of many activities in the temple, or even the other way around; how the temple affected the settlement. There is only a few data about old settlement found in situ in Borobudur site, only abundance of pottery sherds. The analysis applied on to the potteries find during the 2012 excavation had given some information about the old settlement in Borobodur site. The old settlement predicted as resided in the south west area, in the back side of the monument.